Capital gains taxation and house price fluctuations - Clemens Fuest; Bernd Huber; Søren Bo Nielsen (Copenhagen Business School (CBS), Department of Economics, 2006)
Recent years have seen large swings in house prices in many countries. Motivated by housing price variations, proposals for taxing capital gains on housing have repeatedly been put forth. The idea seems to be that such taxes would curb the redistribution occurring between those owning houses and those trying to get into the market for owner-occupied housing. Our paper shows that at least in simple settings, a tax on real capital gains on housing will only lead to even bigger price swings and will not be able to redistribute between people appearing on either side of the housing market.
hdl:10398/7640
Keywords: H23; H24; R31; 330; capital gains tax; housing market; price fluctuations